L.K. Bertram. 2020. The Viking Immigrants: Icelandic North Americans - Christopher Crocker (Scandinavian-Canadian Studies, 2022)
L.K. Bertram. 2020. The Viking Immigrants: Icelandic North Americans. Toronto, Buffalo, London: University of Toronto Press. xv + 245 pages. ISBN: 978-1-4426-1366-9.